2013
DOI: 10.3844/ajassp.2013.767.778
|View full text |Cite
|
Sign up to set email alerts
|

BIO-GUIDED STUDY ON <i>MELASTOMA MALABATHRICUM</i> LINN LEAVES AND ELUCIDATION OF ITS BIOLOGICAL ACTIVITIES

Abstract: The present study aimed to isolate and identify constituents with antibacterial activity from the Methanol extract of Melastoma malabathricum leaves (MMML) through bioassay guided fractionation. Furthermore, the study scoped to evaluate the cytotoxic effects of M. malabathricum leaves fractions for possible protective effect of antoxidative constituents present in the fractions. The MMML extract was fractionated by Vacuum Liquid Chromatography (VLC) to afford M. malabathricum leaves fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…MM plant has been utilized in the treatment of inflammation and rheumatism by the local people in Dibrugarh district, Assam. The plant is rich source of different chemical constituents such as α-amyrin, patriscabatine and auranamide [13], kaempferol-3-O-(2”,6”-di-O-p-trans-coumaroyl)glucoside, quercitrin, Mefloquine, (+) 3,4-Dehydroproline amide, 2-(3,5-Diphenyl-pyrazol-1-yl) benzothiazole, Kaempferol, Kaempferol-3-O-(2”, 6”-di-O-p-trans-coumaroyl)-β-glucopyranoside [14, 52]. …”
Section: Introductionmentioning
confidence: 99%
“…MM plant has been utilized in the treatment of inflammation and rheumatism by the local people in Dibrugarh district, Assam. The plant is rich source of different chemical constituents such as α-amyrin, patriscabatine and auranamide [13], kaempferol-3-O-(2”,6”-di-O-p-trans-coumaroyl)glucoside, quercitrin, Mefloquine, (+) 3,4-Dehydroproline amide, 2-(3,5-Diphenyl-pyrazol-1-yl) benzothiazole, Kaempferol, Kaempferol-3-O-(2”, 6”-di-O-p-trans-coumaroyl)-β-glucopyranoside [14, 52]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have elucidated that K F can inhibit P. aeruginosa growth [6,7]. In regard to this inhibitory effect, the approach of transcriptomic analysis is useful to identify the differentially expressed genes in this bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…Strains of P. aeruginosa are aeruginosa infections are increasingly required and gaining more and more attention [4]. Previous studies by our research group demonstrated that K F can induce P. aeruginosa cell wall damage [6,7]. us, we decided to investigate the gene expression profile of P. aeruginosa growing in kaempferol-3-O-(2′,6′-di-O-trans-p-coumaroyl)-β-D glucopyranoside isolated from Melastoma malabathricum known to locals in Malaysia as "senduduk."…”
Section: Introductionmentioning
confidence: 99%
“…The extract of A.hirtum was fractionated by column chromatography process as reported by Dawang et al [20] using the following mobile phase; n-hexane: Methanol(MeOH) as (10:0, 15:1,9:4,8:2,7: 3,6:4,5:5,4:6,3:7,2:8) and MeOH:Ethanol (EtoAC) (10:0,9:1,8:2, 7:3,6:4,5:5) and the effluent was collected in a small fraction (150cm3) in a beaker. Fractions from crude plant extract were pooled together based on similar profile on Thin Layer Chromatography (TLC, AlugramXtra SIL G/uv 254, MAC HERY-NAGEL GmbH and Co. Kg, Germany) to yield 11 A.hirtum leaf fractions of AF1-AF11 due to variance in polarity and types of constituents extracted [21].However only 1 most effective fraction obtained after preliminary bioassay of the 11 fractions was tested against the isolates.…”
Section: Column Chromatographymentioning
confidence: 99%